Pengembangan LMS Moodle Berbasis PBL Untuk Mengukur Keefektifan Hasil Belajar Kognitif pada Elemen Analisis Data di Smk Sejahtera Surabaya - Eka Yunizar Zaimatus Sa'diyah; Rindu Puspita Wibawa (CV. SINAR HOWUHOWU, 2026)
This research is motivated by the cognitive stagnation of vocational school students in the Data Analysis element, which is mostly limited to lower-order thinking skills (LOTS) and has not met the analytical problem-solving target (C4). This is caused by abstract materials and the use of fragmented digital tools that trigger cognitive overload. As a solution, this study aims to develop and measure the effectiveness of a Moodle Learning Management System (LMS) integrated with Problem Based Learning (PBL) syntax. The method used is Research and Development (R&D) with the ADDIE approach (Analyze, Design, Development, Implementation, Evaluation). The field testing applied a Quasi-Experimental Non-Equivalent Control Group Design involving an experimental class and a control class at SMK Sejahtera Surabaya. The results showed that the product feasibility achieved a